Settlement Types and Community Organization in Northern Canada - Fried, J. (ARCTIC, 1963)
Summarizes 1961-1962 field studies of settlements resulting from post-World War II development in the Northwest Territories. On criteria of community planning, function, and social structure, seven settlement types are distinguished: isolated technical, e.g. weather stations; military; outpost service, e.g. Dorset; serviced native enclave, e.g. Akudlik at Churchill; regional administrative; frontier; and mining. Each type is characterized as to social organization and population. Civil servants, as to their reaction to settlement life, as is the white settlers, and aboriginals are noted danger of arrested cultural transition among the aboriginals.